CONTEMPORARY HEALTH: NAVIGATING MODERN CHALLENGES AND INNOVATIONS IN GLOBAL HEALTHCARE SYSTEMS - Oxyandi, Miming; Fatriansari, Asih; Pranata, Lilik (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2025)
Contemporary health refers to the dynamic intersection of modern medicine, technological innovations, global health challenges, and the evolving understanding of well-being. The rapid pace of scientific discovery, coupled with significant sociopolitical and environmental changes, has reshaped the global healthcare landscape. This article examines the modern trends influencing health systems worldwide, focusing on digital health, mental health awareness, healthcare access disparities, and the integration of artificial intelligence (AI) in patient care. The article explores the impact of these factors on public health outcomes, quality of life, and policymaking. As contemporary health challenges continue to evolve, a multidisciplinary approach involving technology, policy reforms, and global collaboration is essential. The role of emerging trends such as telemedicine, AI-driven diagnostics, and mental health prioritization are discussed in depth. This study draws on recent literature to assess the success of various interventions and highlights areas where improvements can be made. Understanding contemporary health trends is crucial for policymakers, healthcare providers, and communities in adapting to ongoing challenges, ensuring a future that prioritizes equity, accessibility, and quality in healthcare delivery.